The Role of Globalization on CO2 Emission in Vietnam Incorporating Industrialization, Urbanization, GDP per Capita and Energy Use - Phong, Le Hoang; Van, Dang Thi Bach; Bao, Ho Hoang Gia (International Journal of Energy Economics and Policy, 2018)
This study examines the impacts of crucial factors associated with Vietnam’s socio-economic development including globalization, industrialization, urbanization, energy consumption and GDP per capita on carbon dioxide emission. The 31-year data (from 1985 to 2015) is analyzed by Autoregressive Distributed Lag (ARDL) method, and bound test result denotes the long-run relationship between the carbon dioxide emission and its determinants. The long-run and short-run effects can be assessed by the cointegration among the variables and Error Correction Model (ECM) respectively. We find that energy consumption, industrialization and GDP per capita increase carbon dioxide emission in the long-run while, in contrast, globalization negatively influences it, which implies pragmatic suggestions for policymakers in promoting pertinent strategies for sustainable economic development in Vietnam. Keywords: Energy consumption, Carbon dioxide emission, Globalization JEL Classifications: C32, Q43, Q56 DOI: https://doi.org/10.32479/ijeep.7065